Scientific research misconducts: an overview - Arzmi, Mohd Hafiz (IIUM Press, 2021)
Research misconduct is fabrication, falsification, or plagiarism in proposing, performing, or reviewing research, or in reporting research results. It can occur at many stages of the research process. These include during proposal preparation, data collection, analysis and publication. The previous studies reported that 2,047 articles were retracted from PubMed in May 2012, with 67% of the articles due to misconduct. Besides, the percentage of retracted papers in the year of 2012 were reported to increase by 10-fold compared to the total articles retracted in 1975. The data from Retraction Watch on the 31st July 2017 revealed that the US, China, Germany, Japan and India were the top six countries that had articles retracted.